Carta de Roberto H. Todd a José Tous Soto - Todd, Roberto H.; Tous Soto, José (My University, 1924)
Encuentro con Barceló en New York
Keywords: Barceló, Antonio R., 1868-1938; Tous Soto, José, 1874-1933; Montgomery Reily, Emmet, 1866-1954; Puerto Rico--Política y gobierno.